Analysis of Controlling Effect of Temperature–Pressure Conditions on Hydrocarbon Generation of Source Rocks - Guo, Ruichao; Zhang, Guanlong; Zeng, Zhiping; Wang, Qianjun; Zhao, Leqiang; Wang, Jianwei; Yu, Tengfei; Gao, Jianxiong (Frontiers in Earth Science, 2022)
The thermal evolution of source rocks and the generation of oil and gas are not isolated reactions of kerogen pyrolysis, but are comprehensively controlled by many influencing factors. In this study, a large number of high-temperature thermal simulation experiments were carried out to study characteristics of kerogen, e.g. thermal evolution degree and hydrocarbon yield, as well as their influences under the semi-open system, closed system and different temperature-pressure conditions. The results show that the hydrocarbon yield under the low heating rate is higher than that under the high heating rate, and the hydrocarbon generation reaction can be fully carried out under the low heating rate, which is more favorable for hydrocarbon generation; with the increase of pressure in the reaction system, the dominant frequency of activation energy of hydrocarbon generation gradually decreases; in terms of hydrocarbon yield, the oil yield is higher in a high pressure environment, especially the yield of C6-14 component in hydrocarbons is obviously increased, while there is a relatively small difference between the C14+ components.